(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Colorectal carcinoma is a major causes of mortality and morbidity worldwide. Objective: The purpose of the present study was to consider the socio-demographic status and serum CEA level as diagnostic tool for advanced stages of colorectal cancer. Methodology: This analytical cross-sectional study was conducted in the Department of Surgery at Shaheed Ziaur Rahman Medical College Hospital, Bogra during the period of January 2010 to December 2011. Patients age ranged from 15 years to 75 years and above were included in this study. All efforts and available modern technologies including ultrasonography (USG), CT scan, endo-anal USG, chest X-ray were done to detect the primary site and metastasis of colorectal cancer. Result: The most frequent colorectal cancer was detected in 35-44 years age group with 60.0% male and 40.0% female patients. A total number of 41(82%) cases had been suffering from rectal carcinoma and 9(18%) with colonic cancer. Abdominal pain, anorexia, altered bowel habit, per rectal bleeding and abdominal lump were the cardinal features in clinical presentation. This study showed that serum CEA level was raised in 3(11.11%) cases with tumour size 2-5 cm and 21(91.30%) cases with tumor size >5cm. It was observed that serum CEA level was raised in 100% cases of Dukes stage ’D’, 92.31% cases of stage ’C’ and 30.56% cases of stage ’B’ colorectal cancer. The serum CEA level in relation with tumour size and stage has been proved highly significant (p<0.001). Conclusion: Rectal carcinoma is found common than colonic cancer and level of serum CEA is directly related to the cancer stage. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14413 J Shaheed Suhrawardy Med Coll, 2012;4(2):53-56